Bioconversion of Glycerol to Biosurfactant by Halophilic Bacteria Halomonas elongata BK-AG18 - Mieke Alvionita; Rukman Hertadi (Indonesian Journal of Chemistry, 2019)
The increasing production of biodiesel is typically followed by the increasing number of glycerol as co-product. The abundance of glycerol will cause an environmental problem since it can be used as the carbon source for bacterial growth including pathogenic bacteria. In this study, four moderate halophilic bacteria indigenous from Bledug Kuwu Mud Crater, Central Java, Indonesia were screened based on their capability to bioconvert glycerol to biosurfactant. This study found Halomonas elongata BK-AG18 as the potential bacterium that able to perform such bioconversion. The optimum condition for the bioconversion of glycerol into biosurfactant was attained when the bacterial inoculum was grown in the medium containing 2% (v/v) glycerol, 0.3% (w/v) urea, and 5% (w/v) NaCl at 35 °C and pH 6. The resulted biosurfactant has emulsification index (EI24) about 53.6% and CMC about 275 mg/L. Preliminary structural analysis using FTIR and 1H-NMR indicated that biosurfactant produced by H. elongata BK-AG18 was likely a glycolipid type. The biosurfactants have antibacterial activity against Staphylococcus aureus with a minimum inhibitory concentration of 433 mg/L. Our study thus showed that H. elongata BK-AG18 was the potential halophilic bacteria that can bioconvert glycerol into glycolipid type of biosurfactant with antibacterial activity.